PERAN POLISI HUTAN DALAM PENANGGULANGI TINDAK PIDANA ILLEGAL LOGGING DI INDONESIA - Asram AT Jadda (Madani Legal Review, 2019)
This study aims to determine the role of the forest police in overcoming the crime of illegal logging in the forest area of ​​Pinrang Regency and the factors that become obstacles for the forest police in overcoming the crime of illegal logging in the forest area of ​​Pinrang Regency. The research was conducted in Kaseralau Village, Pinrang District Batulappa District, namely in the Pinrang District Forestry Service, by conducting direct interviews with the Head of the Pinrang District Forestry Service, members of the Forest Police and community leaders and reviewing Laws and other literature relating to research. Data analysis was performed using descriptive - qualitative analysis. The findings obtained from this study include: (1) In its implementation, the forest police have not played an optimal role in tackling crime in Pinrang District, especially in the village of Kaseralau. This is because the forest police do not exercise their authority as stipulated in Law Number 41 of 1999 concerning Forestry; (2) Factors of illegal logging in forest areas which become an challenge for forest police to deal with illegal logging in the forest area of ​​Pinrang District, especially in the village of Kaseralau, there are no investigators from the Forestry Office of Pinrang Regency so that all cases of illegal logging are submitted to the Police Pinrang. Another obstacle is the lack of forest police personnel and the lack of operational facilities. In addition, the geography of the forest area of ​​Pinrang District specifically in the village of Kaseralau also affected because the forest area was difficult to reach by the forest police